A method for depolymerizing and upgrading polyester materials to generate dicarboxylic acid esters and boric acid esters
By using heterogeneous solid magnesium-aluminum hydrotalcite catalyst and benzeneboric acid to capture ethylene glycol, the efficient methanolylation reaction of PET and the directional upgrade of ethylene glycol are achieved, and the recovery of ethylene glycol and catalyst recycling in PET depolymerization is solved. The problem has improved the resource utilization efficiency and yield of PET waste plastics.
Patent Information
- Application Number
- CN202310544293.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-15
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2043-05-15
AI Technical Summary
In the existing PET depolymerization technology, ethylene glycol is difficult to separate and recycle, and catalysts are difficult to recycle, resulting in efficient depolymerization and resource utilization efficiency of PET waste plastics, and high catalyst costs, which limits the industrialization progress of PET waste plastics.
Using heterogeneous solid alkali magnesium aluminum hydrotalcite or its derived composite oxide as catalyst, the generated ethylene glycol is captured by phenylboric acid through PET methanolylation reaction, forming a five-membered cyclic boric acid ester, achieving efficient depolymerization of PET and the directional upgrade and recycling of ethylene glycol.
It realizes the efficient methanolylation reaction of PET, the directional recycling of ethylene glycol and the formation of boric acid ester. The catalyst has efficient and simple recycling characteristics, short reaction time and high yield, and is suitable for a variety of PET wastes, reducing Recycling costs of catalysts.
Smart Images

Figure CN116836191B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing dimethyl terephthalate and boric acid ester by depolymerizing PET with high selectivity, and relates to comprehensive utilization of waste resources and cascade utilization of raw materials. More specifically, the present invention relates to a method for depolymerizing various polyester raw materials including PET and polycarbonate with methanol, and obtaining high-yield dicarboxylic acid esters and various five-membered cyclic boric acid esters. Background Art
[0002] Polyethylene terephthalate (PET) is a polymer widely used in plastic packaging and fibers. The "disposable" use characteristics and short service life of PET bottles (usually 6 months) make it the most common plastic waste, accounting for about 10% of the world's total. However, only 42% of PET bottles are recycled, and the remaining 58% of waste plastics end up in landfills or are burned. At present, the main methods for processing PET are thermal recovery, mechanical recovery or chemical recovery, but only chemical recovery can convert polymers into original monomers, fuels or other value-added products, thereby extending the value chain and improving product quality. The chemical depolymerization of PET occurs through hydrolysis, alcoholysis, aminolysis or aminolysis, which involves the selection of different nucleophilic reagents to attack the C=O bond in the polyester. However, the chemical depolymerization can be regarded as a monomer recovery strategy to a certain extent. The ethylene glycol produced in the reaction is difficult to separate and recover due to its high boiling point and is usually abandoned. But the ethylene glycol unit of PET also has great potential for conversion into high-value chemicals and has been used as a precursor material to convert into small molecule carboxylic acids and light olefins with higher added value. Therefore, innovative recycling of ethylene glycol units is an important issue that needs to be urgently addressed in the field of PET depolymerization.
[0003] Historically, most chemical recycling strategies have not been effectively implemented and ultimately failed due to the low economic value of the derived products. To advance the development of this field, it is crucial to simplify the monomer purification procedure and reduce energy consumption. Among various processing methods, dimethyl terephthalate (DMT) derived from PET methanolysis is easier to extract and purify from the reaction system due to its low water solubility, making it a suitable alternative matrix for the synthesis of recycled PET materials or other chemicals. In addition, the methanolysis system has high pollution resistance, making it a cost-effective option for treating complex PET-based waste. However, methanolysis generally requires higher temperatures (generally ≥200°C) to promote the slow decomposition of PET depolymerization, and the product DMT yield is only between 80-85%. In order to pursue a high yield of DMT, there are also a small number of supercritical methanol or microwave-assisted methanolysis system research projects, but considering factors such as equipment operation and economic benefits, it is not recommended. In addition, homogeneous catalysts are used in most reactions, which makes it difficult to separate them from the system, resulting in additional economic costs, which to a certain extent also restricts the industrialization progress of methanolysis of PET waste plastics. Therefore, it is worth paying attention to the development of mild and efficient methanolysis strategies. It can be seen that how to provide an effective PET methanolysis catalytic system, a targeted upgrading and recycling strategy for ethylene glycol during the depolymerization process, and a means to reduce the recycling cost of the catalyst in the catalytic system are problems that need to be urgently solved by technical personnel in this field.
[0004] Cyclic boric acid esters are important organoboron compounds. Due to their good functional group compatibility, simple preparation process of boronic acid derivatives, and low toxicity of boron byproducts, they have been widely used in the efficient construction of drugs and natural products. In addition, boric acid esters show better chemical selectivity and regioselectivity than boric acid in some metal-catalyzed cross-coupling reactions (such as Heck and Suzuki reactions). Usually, boric acid esters are obtained by reversible binding of diols and boric acids. Therefore, aromatic boronic acids can be used to capture EG components from waste PET, thereby solving the problem of ethylene glycol separation and achieving high-value conversion of ethylene glycol. This high-value recovery strategy helps to fully utilize PET waste at the molecular level. The only byproduct is water, which helps to alleviate the consumption of petroleum resources to a certain extent and improve the recycling value of PET waste. Summary of the invention
[0005] Aiming at the needs of depolymerization of PET waste plastics and directional upgrading of products, as well as the shortcomings of the prior art, the present invention provides a method for depolymerizing and upgrading polyester materials to generate dicarboxylic acid esters and boric acid esters. The method uses a heterogeneous solid alkali magnesium aluminum hydrotalcite or a composite oxide derived therefrom to catalyze the methanolysis of PET, and ethylene glycol generated by in-situ capture of phenylboric acid is dehydrated and cyclized to form different types of five-membered cyclic boric acid esters.
[0006] The specific technical solutions adopted by the present invention are as follows:
[0007] A method for depolymerizing and upgrading polyester materials to generate dicarboxylic acid esters and boric acid esters, comprising:
[0008] S1. Place crushed polyester material, aromatic boronic acid, heterogeneous catalyst and methanol solvent in a reaction kettle; wherein the polyester material is polyethylene terephthalate (PET), polypropylene carbonate, polyethylene adipate or polyethylene succinate; the aromatic boronic acid is phenylboric acid, p-methylphenylboric acid, 3-methylphenylboric acid or 4-fluorophenylboric acid; the heterogeneous catalyst is magnesium aluminum hydrotalcite or magnesium aluminum hydrotalcite-derived composite oxide calcined at 350-600° C. and having a Mg / Al ratio of (4-1):1;
[0009] S2, placing the reactor at a depolymerization temperature of 160-200° C. for 1-4 hours to carry out a depolymerization reaction, and cooling the temperature to room temperature after the reaction is completed to obtain a depolymerization product containing dicarboxylic acid ester and aryl borate ester.
[0010] Taking PET as an example, the reaction equation of the above depolymerization reaction can be expressed as:
[0011]
[0012] Preferably, the added amount of the aromatic boronic acid is the same as the molar amount of the polyester material.
[0013] Preferably, the heterogeneous catalyst is added in an amount of 0.05 wt% to 0.5 wt% of the polyester material.
[0014] Preferably, the added amount of the methanol solvent is 3-6 mL / mmol of the polyester material.
[0015] Preferably, the polyester material is waste polyethylene terephthalate (PET), and the waste needs to be pre-crushed into centimeter-level flakes, particles or powders before being added to the reactor, which can ensure the resource utilization effect of waste PET materials and obtain dimethyl terephthalate and aromatic borate (ABE) in a targeted manner with high yield.
[0016] Preferably, the waste is in the form of PET waste bottles, PET matrix waste films, PET colored bundles or PET non-woven fabrics.
[0017] Preferably, the calcination temperature of the heterogeneous catalyst is 450-500°C.
[0018] Preferably, the calcination time of the heterogeneous catalyst is 4 to 8 hours.
[0019] Preferably, the Mg / Al ratio in the heterogeneous catalyst is 4:1.
[0020] Preferably, the depolymerization temperature is 180°C.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The heterogeneous solid magnesium-aluminum hydrotalcite-derived composite oxide catalyst used in the present invention has the advantages of high efficiency, simple recovery, and multiple recycling, and can promote the methanolysis reaction of PET and the directional upgrading and recovery of ethylene glycol in a relatively short time.
[0023] (2) The waste plastic PET methanol depolymerization strategy developed by the present invention has the advantages of short reaction time and high catalytic efficiency, and can complete the directional conversion process of PET to DMT and ethylene glycol to borate ester with a yield of 99% under standard reaction conditions. This strategy has a wide range of applications, and the types of waste PET raw materials are varied. Various types of PET waste materials such as various types of PET waste bottles, PET matrix waste films, PET colored ropes and PET non-woven fabrics can all be efficiently upgraded in a short time.
[0024] (3) The PET waste plastic matrix material of the present invention can be replaced by various polyesters and polycarbonates having similar diol units, such as polyethylene succinate, polyethylene adipate and polypropylene carbonate, which to a certain extent shows the high applicability of the strategy and further broadens the scope of waste plastic treatment materials. Under the premise of ensuring high depolymerization efficiency and rapid reaction time, the corresponding conversion can be completed to obtain dicarboxylic acid esters and boric acid esters. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a demonstration of the catalyst recycling effect of the present invention. DETAILED DESCRIPTION
[0026] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, a detailed description is given below through specific embodiments. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below. The technical features in each embodiment of the present invention can be combined accordingly without conflicting with each other.
[0027] Example 1
[0028] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.192 grams of PET powder (1 mmol), 0.13 grams of p-methylphenylboric acid (1 mmol), 0.03 grams of commercially available magnesium aluminum hydrotalcite (Mg / Al=3:1) and 5 mL of methanol were added. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 180°C and reacted at this temperature for 2 hours. After the reaction was completed, the temperature was cooled to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured for yield by GC, with mesitylene as the internal standard. The results showed that the PET decomposition rate of this embodiment was 100%, the yield of dimethyl terephthalate was 87%, and the yield of p-methylphenylboric acid ester was 90%.
[0029] It should be noted that the catalyst in the present invention must be a composite oxide derived from magnesium aluminum hydrotalcite, but the Mg / Al ratio can be adjusted to change the catalytic performance, and Mg / Al can generally be controlled to (4-1):1. Experiments have shown that the composite oxide with a Mg / Al ratio of 4:1 can achieve the best depolymerization reaction catalytic performance. In addition, commercially available hydrotalcite materials can also be used as catalyst precursors in the experiment, and the derived composite oxides can be synthesized by calcination as reaction catalysts. The following is another preferred preparation method of magnesium aluminum hydrotalcite-derived composite oxide catalysts shown in Example 2.
[0030] Example 2
[0031] Preparation of heterogeneous catalyst magnesium aluminum hydrotalcite derived composite oxides (LDOs):
[0032] Various types of hydrotalcites were prepared by coprecipitation at a constant pH of 10, and then magnesium-aluminum hydrotalcite-derived composite oxides (LDOs) were prepared by calcination. First, two solutions were prepared as follows: flask A: 6.80 g (0.08 mol) of NaNO3 was dissolved in 50 mL of deionized water, and beaker B: 15.38 g of Mg(NO3)26H2O (0.060 mol) and 5.63 g of Al(NO3)39H2O (0.015 mol) were dissolved in 50 mL of deionized water. The contents of beaker B were added to flask A in a dropwise manner, and the pH value was maintained at 10 using a 1 mol / L NaOH solution during the dropwise addition. The resulting mixed solution was reacted at ambient temperature for two hours. Subsequently, the mixed solution was heated to 80°C and stirred and refluxed for 12 hours. The resulting precipitate was filtered, washed with hot deionized water, and then dried in a vacuum oven at 80°C for 24 hours to obtain a layered double hydroxide (Mg4-Al1-LDH). After the dried Mg4-Al1-LDH is ground into powder, it is calcined, specifically including heating to 450°C in an argon flow in a tube furnace for 4 hours and 500°C for another 4 hours. The composite oxide obtained after the calcination is magnesium aluminum hydrotalcite derived composite oxide (Mg4-Al1-LDO). For the convenience of description, the final product is named LDO-I catalyst and is used as the heterogeneous catalyst in subsequent Examples 3 to 9. LDO-I can be stored under ambient air conditions.
[0033] Example 3
[0034] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.192 g of CR-pure PET powder (1 mmol), 0.13 g of p-methylphenylboric acid (1 mmol), 0.03 g of catalyst LDO-Ⅰ, and 5 mL of methanol were added. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 180°C and reacted at this temperature for 2 hours. After the reaction was completed, the temperature was cooled to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured for yield by GC, with mesitylene as the internal standard. The results showed that the PET decomposition rate of this embodiment was 100%, the yield of dimethyl terephthalate was 99%, and the yield of p-methylphenylboric acid ester was 99%.
[0035] In addition, in order to prove the recyclability of the catalyst in the present invention, the catalyst LDO-Ⅰ after the reaction was separated and recovered, and after rinsing and impurity removal, it was dried at 150°C, and the obtained heterogeneous solid magnesium aluminum hydrotalcite-derived composite oxide catalyst was directly recycled to the next reaction. The test results are as follows: Figure 1As shown, after repeated use for 6 times, the yields of p-toluene borate and dimethyl terephthalate still reached 85% and 99% respectively. After repeated use for 6 times, the catalyst was heated to 450-500°C for calcination again, and the catalytic effect of the catalyst was basically restored. After recovery, the yields of p-toluene borate and dimethyl terephthalate were 98% and 99% respectively when depolymerization was carried out.
[0036] Example 4
[0037] Discarded PET plastic bottles (Coca-Cola, Pepsi and Nongfu Spring brands) were crushed to centimeter level in advance, and then 0.192 grams of PET plastic bottles were crushed to centimeter level (1mmol), 0.13 grams of p-methylphenylboric acid (1mmol), 0.03 grams of catalyst LDO-Ⅰ and 5mL of methanol were added to an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple and a programmable temperature controller. After placing the autoclave reactor, stirring and heating were turned on. The reaction system was heated to 180°C and reacted at this temperature for 3h. After the reaction was completed, it was cooled to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured for yield by GC, with mesitylene as the internal standard. The results showed that the PET decomposition rate of this embodiment was 100%, the yield of dimethyl terephthalate was 99%, and the yield of p-methylphenyl borate was 99%.
[0038] Example 5
[0039] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.192 grams of PET powder (1 mmol), 0.136 grams of 3-methylphenylboric acid (1 mmol), 0.03 grams of catalyst LDO-Ⅰ, and 5 mL of methanol were added. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 180°C and reacted at this temperature for 2 hours. After the reaction was completed, the temperature was cooled to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured for yield by GC, with mesitylene as the internal standard. The results showed that the PET decomposition rate of this embodiment was 100%, the yield of dimethyl terephthalate was 99%, and the yield of 3-methylphenylboric acid ester was 99%.
[0040] Example 6
[0041] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.192 grams of PET powder (1 mmol), 0.139 grams of 4-fluorophenylboric acid (1 mmol), 0.03 grams of catalyst LDO-Ⅰ, and 5 mL of methanol were added. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 180°C and reacted at this temperature for 2 hours. After the reaction was completed, the temperature was cooled to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured for yield by GC, with mesitylene as the internal standard. The results showed that the PET decomposition rate of this embodiment was 100%, the yield of dimethyl terephthalate was 99%, and the yield of p-fluorophenyl borate was 99%.
[0042] Example 7
[0043] 0.102 g of polypropylene carbonate particles (1 mmol), 0.136 g of p-methylphenyl boric acid (1 mmol), 0.03 g of catalyst LDO-Ⅰ and 5 mL of methanol were added to an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple and a programmable temperature controller. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 180°C and reacted at this temperature for 2 hours. After the reaction was completed, the temperature was cooled to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured for yield by GC, with mesitylene as the internal standard. The results showed that the decomposition rate of polypropylene carbonate particles in this embodiment was 100%, dimethyl carbonate and p-methylphenyl borate were produced, and the yield of p-methylphenyl borate was 95%.
[0044] Example 8
[0045] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.172 g of polyethylene adipate (1 mmol), 0.136 g of p-methylphenylboric acid (1 mmol), 0.03 g of catalyst LDO-Ⅰ, and 5 mL of methanol were added. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 180°C and reacted at this temperature for 2 hours. After the reaction was completed, the temperature was cooled to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured for yield by GC, with mesitylene as the internal standard. The results showed that the decomposition rate of polyethylene adipate in this embodiment was 100%, the yield of dimethyl adipate was 98%, and the yield of p-methylphenylboric acid was 99%.
[0046] Example 9
[0047] 0.144 g of polyethylene succinate (1 mmol), 0.136 g of p-methylphenyl boric acid (1 mmol), 0.03 g of catalyst LDO-Ⅰ and 5 mL of methanol were added to an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple and a programmable temperature controller. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 180 ° C and reacted at this temperature for 1 hour. After the reaction was completed, the temperature was cooled to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured by GC for yield, with mesitylene as an internal standard. The results showed that the decomposition rate of polyethylene succinate in this embodiment was 100%, the yield of dimethyl succinate was 88%, and the yield of p-methylphenyl borate was 99%.
[0048] The above-described embodiment is only a preferred solution of the present invention, but it is not intended to limit the present invention. A person skilled in the relevant technical field may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.
Claims
1. A method for depolymerizing and upgrading polyester materials to generate dicarboxylic acid esters and boric acid esters, characterized in that: include: S1. Put crushed polyester material, aromatic boronic acid, heterogeneous catalyst and methanol solvent into a reaction kettle; wherein the polyester material is polyethylene terephthalate (PET), polypropylene carbonate, polyethylene adipate or polyethylene succinate; the aromatic boronic acid is phenylboric acid, p-methylphenylboric acid, 3-methylphenylboric acid or 4-fluorophenylboric acid; the heterogeneous catalyst is magnesium aluminum hydrotalcite derived composite oxide, and the preparation method thereof is as follows: dissolve 6.80 g of NaNO3 in 50 mL of deionized water to obtain a first solution; dissolve 15.38 g of Mg(NO3)26H2O and 5.63 g of Al(NO3)39H2O in 50 mL of deionized water to obtain a second solution; add the second solution to the first solution in a dropwise manner, and use 1 mol / L NaOH solution to maintain a controlled pH value of 10 during the dropwise addition process, and the obtained mixed solution is reacted at ambient temperature for two hours; Subsequently, the mixed solution was heated to 80° C. and kept stirring and refluxing for 12 hours, and the obtained precipitate was filtered, washed with hot deionized water, and then dried in a vacuum drying oven at 80° C. for 24 hours to obtain a layered double hydroxide; the dried layered double hydroxide was ground into powder, and then heated to 450° C. in an argon flow in a tube furnace and maintained for 4 hours, and then heated to 500° C. and maintained for another 4 hours, and after completing the calcination treatment, a magnesium-aluminum hydrotalcite-derived composite oxide was obtained; S2, placing the reactor at a depolymerization temperature of 160-200° C. for 1-4 hours to carry out a depolymerization reaction, and cooling the temperature to room temperature after the reaction is completed to obtain a depolymerization product containing dicarboxylic acid ester and aromatic boric acid ester; The dicarboxylic acid ester is dimethyl terephthalate, dimethyl carbonate, dimethyl adipate or dimethyl succinate; The aryl borate is 3-methylphenyl borate, p-fluorophenyl borate or p-methylphenyl borate.
2. The method for upgrading polyester materials to produce dimethyl terephthalate and borate esters according to claim 1, characterized in that: The added amount of the arylboronic acid is the same as the molar amount of the polyester material.
3. The method for upgrading polyester materials to produce dimethyl terephthalate and borate esters according to claim 1, characterized in that: The heterogeneous catalyst is added in an amount of 0.05 wt% to 0.5 wt% of the polyester material.
4. The method for upgrading polyester materials to produce dimethyl terephthalate and borate esters as claimed in claim 1, characterized in that: The amount of the methanol solvent added is 3-6 mL / mmol of the polyester material.
5. The method for upgrading polyester materials to produce dimethyl terephthalate and borate esters as claimed in claim 1, characterized in that: The polyester material is waste made of polyethylene terephthalate (PET), and the waste needs to be broken into centimeter-sized flakes, particles or powder before being added to the reactor.
6. The method for upgrading polyester materials to produce dimethyl terephthalate and borate esters as claimed in claim 5, characterized in that: The waste is in the form of PET waste bottles, PET matrix waste films, PET colored bundles or PET non-woven fabrics.
7. The method for upgrading polyester materials to produce dimethyl terephthalate and borate esters as claimed in claim 1, characterized in that: The depolymerization temperature is 180°C.